Capacity building for whole genome sequencing of Mycobacterium tuberculosis and bioinformatics in high TB burden countries. Issue 4 (3rd October 2020) - Rivière, Emmanuel; Heupink, Tim H; Ismail, Nabila; Dippenaar, Anzaan; Clarke, Charlene; Abebe, Gemeda; Heusden, Peter; Warren, Rob; Meehan, Conor J; Van Rie, Annelies
Abstract: Background: Whole genome sequencing (WGS) is increasingly used for Mycobacterium tuberculosis ( Mtb ) research. Countries with the highest tuberculosis (TB) burden face important challenges to integrate WGS into surveillance and research. Methods: We assessed the global status of Mtb WGS and developed a 3-week training course coupled with long-term mentoring and WGS infrastructure building. Training focused on genome sequencing, bioinformatics and development of a locally relevant WGS research project. The aim of the long-term mentoring was to support trainees in project implementation and funding acquisition. The focus of WGS infrastructure building was on the DNA extraction process and bioinformatics. Findings: Compared to their TB burden, Asia and Africa are grossly underrepresented in Mtb WGS research. Challenges faced resulted in adaptations to the training, mentoring and infrastructure building. Out-of-date laptop hardware and operating systems were overcome by using online tools and a Galaxy WGS analysis pipeline. A case studies approach created a safe atmosphere for students to formulate and defend opinions. Because quality DNA extraction is paramount for WGS, a biosafety level 3 and general laboratory skill training session were added, use of commercial DNA extraction kits was introduced and a 2-week training in a highly equipped laboratory was combined with a 1-week training in the local setting. Interpretation: By developing and sharing the components of and experiences with a sequencing and bioinformatics training program, we hope to stimulate capacity building programs for Mtb WGS and empower high-burden countries to play an important role in WGS-based TB surveillance and research.